Numerical Simulation of NAPL Vapor Transport in Air - Pártl, Ondřej; Beneš, Michal; Frolkovič, Peter (Proceedings of the Conference Algoritmy, 2016)
We present a mathematical and numerical model for non-isothermal, compressible flow of a mixture of two ideal gases subject to gravity. The mathematical model is based on balance equations for mass, momentum and energy combined with the ideal gas equation of state. The numerical model is based on the method of lines; the spatial discretization is carried out by means of the control volume based finite element method, and for the time integration, the Runge-Kutta-Merson method is used. Finally, we present preliminary results of numerical experiments that illustrate the ability of our numerical scheme.